Barcode colorido compatível com o decodificador padrão do QR code - Bortoluzzi, Matias Américo (2015)
Motivated by a number of potential applications for high data-density barcodes that can be easily photographed and decoded by smartphones, and analyzing the distortion imposed on a barcode by phone photography, this work presents the design of a new colored two-dimensional barcode compatible with the QR Code decoder. The data is independently encoded into three monochrome barcodes which are then combined so that the new barcode lead to a three-fold increase in data rate compared to the corresponding monochrome barcode. This methodology not only facilitates the decoding but also allows the re-use of optimizations and improvements developed for monochrome QR Codes. In order to minimize the channel impairments, we use reference colors spatially distribuited around the barcode, promoting a meaningful robustness improvement with low computational cost. Furthermore, we analised the acceptable ranges of image channel distortion parameters that are printer, capture condition and camera dependent.